Prevalence of Hepatitis B Virus (HBV) and Hepatitis C Virus (HCV) Infections among Blood Donors at Al-Thawra Hospital Sana'a City-Yemen - Alodini, Abdulaziz Q. (University of Science and Technology, Sana'a, 2014)
Background: Hepatitis is a disease of the liver caused by the infectious and non-infectious agents. Hepatitis B and C are major public health problems worldwide. Aim: The aim of the study was to estimate the prevalence of hepatitis B and hepatitis C viruses among voluntary of healthy blood donors at Al-Thawra Hospital Sana'a City - Yemen, during February to April 2010. Methods: The data from Blood bank in Al-Thawra Hospital were collected and analyzed. All samples were tested by Enzymes Linked Immunosorbent Assay (ELISA) test. Results: Out of 3000 samples of the blood donors, 157 (5.23%) were positive. From overall positive samples, 63 (2.1%) were HBsAg positive, 90 (3.0%) were anti-HCV positive while 4 (0.13%) samples were positive for both HBs Ag and anti-HCV. Conclusion: Blood donors at Al-Thawra Hospital Sana'a have a lower prevalence for infection with HBV and HCV compared to other Arabic countries.